Divas : Mathilde Marchesi and her pupils - Neill, Roger (NewSouth Publishing, 2016)
The incredible story of singing teacher extraordinaire Mathilde Marchesi who trained more international opera stars than anyone before or since. Who was Mathilde Marchesi? How did she become a byword internationally for vocal excellence and operatic success? What was her formula? And how did she produce prima donnas on such a consistent basis?From nineteenth-century Vienna to Paris high society, Roger Neill traces Marchesi's extraordinary five-decade career and introduces a remarkable cast of characters - Felix Mendelssohn, Franz Liszt and the pupils who crossed the globe to study with her, including Dame Nellie Melba. He reveals the phenomenally successful singing method that is her legacy, with Joan Sutherland, Kiri Te Kanawa and Meryl Streep all taught by pupils of Marchesi.